ANALISIS SONKEIGO DAN KENJOUGO DALAM ANIME VIOLET EVERGARDEN KARYA KANA AKATSUKI - Riga Widya Nanda; Nova Yulia (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2025)
This research was aimed to describing the types of keigo, especially sonkeigo and kenjougo, and also the meaning of sonkeigo and kenjougo in the anime entitled Violet Evergarden by Kana Akatsuki. This research was a qualitative research with descriptive method and the source of the data in this study was an anime called Violet Evergarden, from episode 10 through episode 13.  Moreover, the data were vocabulary and sentences containing sonkeigo and kenjougo that found in the anime. The results of this research were four types of sonkeigo and three types of kenjougo that are often used in the four episodes. The first was type of sonkeigo that consists of special verbs with a total of 8 data points, verbs with renryoukei patterns with 3 data points, special nouns with 7 data points, and then prefixes and suffixes with 57 data points. Followed by the type of kenjougo, which consists of 13 data points for special verbs, 2 data points for patterned verbs, and 3 data points for renryoukei patterned verbs. Then, the meaning of sonkeigo and kenjougo that spoken by the main character, Violet Evergarden, and also by the other characters was tends to express their respect for their opponent.